Association Between Eating Habit, Sedentary Lifestyle, and Place of Living with Nutritional Status Among College Students at Sebelas Maret University - Reny Rahmawati; Ida Nurwati; Budiyanti Wiboworini (Poltekkes Kemenkes Palu, 2023)
Advances in technology cause shifts in trends, changes in eating patterns, and sedentary activities in college students can impact nutritional status. This study aimed to analyze the relationship between eating habits, sedentary lifestyle, and place of residence on the nutritional status of Sebelas Maret University students. This is was a quantitative analytical study with a cross-sectional design. Study samples were selected using an accidental sampling technique, which obtained 206 samples aged 17-29 years. The research was conducted in March-April 2023. Eating habits were measured using a questionnaire that had gone through reliability and validation tests and sedentary data using the Adolescent Sedentary Activity Questionnaire (ASAQ) instrument. Bivariate data were analyzed using the Chi-Square test. The results showed that there was a significant relationship between eating habits (p<0.00), sedentary lifestyle (p<0.00), and place of residence (p<0.015) and the nutritional status of students. 11.2% were overweight and 52.4% of students were obese. It was concluded that eating habits, sedentary lifestyle, and place of residence are related to the nutritional status of students at Sebelas Maret University. Future researchers should add indicators of the type, amount, and frequency of food consumed to the eating habits variable to deepen the research results.